Scaling of the magnetic entropy change in skyrmion material Fe0.5Co0.5Si. (October 2017) - Han, Hui; Menzel, Dirk; Liu, Wei; Ling, Langsheng; Du, Haifeng; Pi, Li; Zhang, Changjin; Zhang, Lei; Zhang, Yuheng
Graphical abstract: Highlights: The Δ S M ( T, H ) curves under high field collapse into a universal curve independent of temperature. The Δ S M ( T, H ) curves under low field cannot be scaled into a single curve. The scaling investigation of Δ S M ( T, H ) curves indicates the phase transition exhibits a first order characteristic in low field, which is suppressed into a second one under high field. Abstract: The magnetic entropy change [Δ S M ( T, H )] around the phase transition temperature T C is investigated by the scaling method for Fe0.5 Co0.5 Si, which exhibits a Skyrmion phase below T C . The parameters of Δ S M ( T, H ) exhibit field dependent behaviors. The Δ S M ( T, H ) curves under high field can be well scaled into a single universal curve independent of external field and temperature. However, Δ S M ( T, H ) curves under low field become divergent just below T C, which indicates a characteristic of first-order transition. The scaling investigation of Δ S M ( T, H ) curves indicates that the phase transition in Fe0.5 Co0.5 Si is of a weak first-order type in low field region, while it is driven into a second-order one under high field. This weak first-order phase transition in low field region resembles that in typical skyrmion system MnSi which is caused by the critical fluctuation. The result suggests that critical fluctuation plays an important role in the phase transition and formation of skyrmion state.